2004
DOI: 10.3748/wjg.v10.i1.73
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of nitric oxide induced by ischemic preconditioning on reperfusion injury of rat liver graft

Abstract: AIM: Ischemic preconditioning (IP) is a brief ischemic episode, which confers a state of protection against the subsequent long-term ischemia-reperfusion injuries. However, little is known regarding the use of IP before the sustained cold storage and liver transplantation. The present study was designed to evaluate the protective effect of IP on the long-term preservation of liver graft and the prolonged anhepatic-phase injury. METHODS:Male Sprague-Dawley rats were used as donors and recipients of orthotopic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
8
1
1
Order By: Relevance
“…In the literature, there were several studies using different IP application times, such 5-10 minutes of Pp, followed by 5-10 minutes of deflation, but none of them compare the different application times. [31][32][33] In the present study, a comparison of the IP 5-minutes and IP 10-minutes groups, in terms of oxidative stress response, demonstrated that there was no statistical difference between the IP groups. Consequently, our findings suggest that 5 minutes of an IP period is as effective as 10 minutes of an IP period in preventing the harmful effects of Pp in the laparoscopic rat model.…”
Section: The Ideal Time For Ischemic Preconditioning 143contrasting
confidence: 50%
“…In the literature, there were several studies using different IP application times, such 5-10 minutes of Pp, followed by 5-10 minutes of deflation, but none of them compare the different application times. [31][32][33] In the present study, a comparison of the IP 5-minutes and IP 10-minutes groups, in terms of oxidative stress response, demonstrated that there was no statistical difference between the IP groups. Consequently, our findings suggest that 5 minutes of an IP period is as effective as 10 minutes of an IP period in preventing the harmful effects of Pp in the laparoscopic rat model.…”
Section: The Ideal Time For Ischemic Preconditioning 143contrasting
confidence: 50%
“…Endothelial NOS is present in liver endothelial cells, and responsible for the NO production in early preconditioning [30] . iNOS is present in all liver cell types and the source of NO in late preconditioning [31] . NO produced by endothelial cells play an important role in maintaining the caliber of blood vessels and its reduced release is one of the earliest signs of reperfusion induced by endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, eNOS‐derived NO has also been shown to decrease hepatic aggregation of neutrophils . In a separate animal OLT model, it was shown that endogenous NO reduces the rise of cold IR‐induced TNF‐α expression . Moreover, endogenous NO also limits the rise and inhibits the action of another pro‐inflammatory cytokine, IL‐1α, in reduced‐size OLT, and in parallel, decreases hepatic tissue oxidative damage .…”
Section: Endogenous Nomentioning
confidence: 99%